TOGOG TUALEN MAKETU DI PURA TAMAN BAKA BANJAR PENGAMBANGAN BATUBULAN GIANYAR (Perspektif Aksiologi) - Ni Kadek Rista Windiadnyani; Jro Ayu Ningrat; Ni Luh Gede Wariati (Sanjiwani: Jurnal Filsafat, 2022)
In general, Tualen is in a wayang, but at Taman Baka Temple it appears in the form of a statue using a Ketu. When viewed in the wayang concept, this has transcended the power of a king who was adored by his people. The status of this Tualen is very different, beyond the tiers of color in Hinduism. So the existence of Tualen Maketu needs to be studied to find out how the concept of Tualen actually is. This study is included in qualitative research with the research method used, namely observation, and interviews. So that the results obtained, namely, ethical values ​​lead to the habit of offering the uterine tulung squeeze with the Wayang Klupak Tiying when it fell in Batubulan. In addition, good actions seen from the figure of Tualen who has noble and wise qualities raise a moral aspect. Aesthetic value, namely the figure of Tualen appeared in the form of a statue made of solid stone, with approximately one meter high. Tualen Maketu is a Bhujangga who is made Bhagawanta who knows all activities. Socio-cultural values, namely the existence of Tualen Maketu, bring changes in people's lives.